E-Rulemaking’s Democratic Transformation: Anticipated, Actual, and Potential - Herz, Michael (Revue internationale des Gouvernements Ouverts, 2016)
Notice-and-comment rulemaking is often held out as the purest example of participatory democracy in actual American governance. K.C. Davis called notice-and-comment rulemaking the “most democratic of procedures” because all may participate. Regulators are required to accept comments from any interested person and consider and respond to them before making a final decision. Direct public engagement has been seen as an antidote to the democracy deficit that plagues policymaking by unelected bureaucrats. Central to this conception is a belief that the comment process will involve a meaningful exchange of views. In the words of the DC Circuit, notice and comment involves “an exchange of views, information, and criticism between interested persons and the agency.” Indeed, it is this broad participation and exchange that is seen as legitimating the resulting regulations. Of course, the reality has always fallen far short of these ideals. Many anticipated that electronic rulemaking would enable more democratic rulemaking, finally allowing effective and broad public participation. This has not in fact happened. This paper reviews the course of e-rulemaking in the United States and offers some suggestions for how it might be restructured in a more limited, but more meaningful, democratic way.